Economics and violence against children, findings from the Violence Against Children Survey in Nigeria. (November 2018) - Miller, Gabrielle F.; Chiang, Laura; Hollis, NaTasha
Abstract: This study seeks to assess the impact of economic factors on sexual, emotional, and physical violence on Nigerian children and adolescents aged 13–24 years. Data collected from the Nigerian Violence Against Children Survey (VACS), a national, cross-sectional household survey of females and males aged 13–24 years were used to examine sexual, emotional, and physical violence victimization. Data were collected on household economic status, e.g., flooring and roofing materials, transportation. A poverty index was developed using the Simple Poverty Scorecard ™ for Nigeria to determine the impact that economic factors have on these violence measures. Children aged 13–17 years in households with high economic status (ES) were 1.81, 1.78, and 4.91 times, more likely to experience sexual, emotional, and physical violence, respectively, within the last 12 months than those in the lowest ES. Individuals aged 18–24 years in households with high ES were 1.62 and 1.41 times more likely to experience emotional and physical violence, respectively, prior to age 18 than those in the lowest ES. Individuals aged 18–24 years in households with middle or high ES were 1.65 and 1.96, respectively, times more likely to experience physical violence prior to age 18 than those in the lowest ES. Highest tertile ES was significantly associated with sexual, emotional, and physical violence among Nigerians aged 13–24 years. Further research is needed to determine the cause of increased violence amongst high ES households. Targeted interventions towards this ES class are recommended to reduce violence against children in Nigeria.